Donor Specificity but Not Broadness of Sensitization Is Associated With Antibody‐Mediated Rejection and Graft Loss in Renal Allograft Recipients. Issue 8 (27th March 2017) - Wehmeier, C.; Hönger, G.; Cun, H.; Amico, P.; Hirt‐Minkowski, P.; Georgalis, A.; Hopfer, H.; Dickenmann, M.; Steiger, J.; Schaub, S.
Abstract : Panel‐reactive antibodies are widely regarded as an important immunological risk factor for rejection and graft loss. The broadness of sensitization against HLA is most appropriately measured by the "calculated population‐reactive antibodies" (cPRA) value. In this study, we investigated whether cPRA represent an immunological risk in times of sensitive and accurate determination of pretransplantation donor‐specific HLA antibodies (DSA). Five hundred twenty‐seven consecutive transplantations were divided into four groups: cPRA 0% (n = 250), cPRA 1–50% (n = 129), cPRA 51–100% (n = 43), and DSA (n = 105). Patients without DSA were considered as normal risk and received standard immunosuppression without T cell–depleting induction. Patients with DSA received an enhanced induction therapy and maintenance immunosuppression. Surveillance biopsies were performed at 3 and 6 months. Median follow‐up was 5.7 years. Among the three cPRA groups, there were no differences regarding the 1‐year incidence of ABMR (p = 0.16) and TCMR (p = 0.75). The 5‐year allograft survival rates were similar and around 87% (p = 0.28). The estimated glomerular filtration rate at last follow‐up was 50–53 mL/min (p = 0.45). On multivariable Cox proportional hazard analysis, the strongest independent predictor for ABMR and (death‐censored) graft survival was pretransplantation DSA. cPRA were not predictive for ABMR, TCMR, or (death‐censored) graft survival. We conclude that with current DSA assignment, the broadness of sensitization measured by cPRA does not imply an immunological risk. Abstract : This study investigates the impact of the broadness of sensitization measured by calculated population‐reactive antibodies on pertinent outcomes, and challenges its use as an immunological risk factor in renal allograft recipients.